Malaria after international travel : a GeoSentinel analysis, 2003–2016 - Angelo, Kristina M. (2018)
Background: More than 30,000 malaria cases are reported annually among international travellers. Despite improvements in malaria control, malaria continues to threaten travellers due to inaccurate perception of risk and sub-optimal pre-travel preparation. Methods: Records with a confirmed malaria diagnosis after travel from January 2003 to July 2016 were obtained from GeoSentinel, a global surveillance network of travel and tropical medicine providers that monitors travel-related morbidity. Records were excluded if exposure country was missing or unascertainable or if there was a concomitant acute diagnosis unrelated to malaria. Records were analyzed to describe the demographic and clinical characteristics of international travellers with malaria. Results: There were 5689 travellers included; 325 were children <18 years. More than half (53%) were visiting friends and relatives (VFRs). Most (83%) were exposed in sub-Saharan Africa. The median trip duration was 32 days (interquartile range 20–75); 53% did not have a pre-travel visit. More than half (62%) were hospitalized; children were hospitalized more frequently than adults (73 and 62%, respectively). Ninety-two per cent had a single Plasmodium species diagnosis, most frequently Plasmodium falciparum (4011; 76%). Travellers with P. falciparum were most frequently VFRs (60%). More than 40% of travellers with a trip duration ≤7 days had Plasmodium vivax. There were 444 (8%) travellers with severe malaria; 31 children had severe malaria. Twelve travellers died. Conclusion: Malaria remains a serious threat to international travellers. Efforts must focus on preventive strategies aimed on children and VFRs, and chemoprophylaxis access and preventive measure adherence should be emphasized.